2020
DOI: 10.1002/aur.2399
|View full text |Cite
|
Sign up to set email alerts
|

Using the NIH Toolbox to Assess Cognition in Adolescents and Young Adults with Autism Spectrum Disorders

Abstract: Despite the clinically significant impact of executive dysfunction on the outcomes of adolescents and young adults with autism spectrum disorders (ASD), we lack a clear understanding of its prevalence, profile, and development. To address this gap, we administered the NIH Toolbox Cognition Battery to a cross‐sectional Intelligence Quotient (IQ) case‐matched cohort with ASD (n = 66) and typical development (TD; n = 66) ages 12–22. We used a general linear model framework to examine group differences in task per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 72 publications
1
3
0
Order By: Relevance
“…It is worth mentioning that the lowest scores in these studies were between the mean and 1 standard deviation below [ 35 ]. In contrast to these findings, adolescents with Tourette’s syndrome did not show average results below the 50th percentile, with the lowest scores in list sorting working memory [ 34 ], which have also been corroborated in other studies [ 36 ]. These studies exemplify that the neurocognitive batteries can show discrete patterns of subtle deficits in areas that can be disorder specific.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…It is worth mentioning that the lowest scores in these studies were between the mean and 1 standard deviation below [ 35 ]. In contrast to these findings, adolescents with Tourette’s syndrome did not show average results below the 50th percentile, with the lowest scores in list sorting working memory [ 34 ], which have also been corroborated in other studies [ 36 ]. These studies exemplify that the neurocognitive batteries can show discrete patterns of subtle deficits in areas that can be disorder specific.…”
Section: Discussionsupporting
confidence: 79%
“…The NIH toolbox has been used to assess neurocognitive function in children and adolescents with other conditions and has also found pattern deficiencies that seem to be condition specific. For instance, adolescents and young adults with autism spectrum have demonstrated that, among the other tests, the lowest scores have been found in pattern comparison processing speed [ 34 ], findings that have been corroborated in adults [ 35 ]. Slower processing speed can contribute to some aspects of psychosocial functioning found in patients with autism.…”
Section: Discussionmentioning
confidence: 99%
“…Combining VNS with the CMRST provides a way to further explore the mechanisms through which vagal afferents can modulate cognitive flexibility. Behavioral rigidity and perseveration occur in a number of neuropsychiatric disorders, including schizophrenia, substance use disorders, obsessive compulsive disorder, and autism [ 57 , 58 , 59 , 60 ]. Therapeutic strategies that enhance cognitive flexibility could therefore have important clinical implications.…”
Section: Discussionmentioning
confidence: 99%
“…Neurocognitive profiles are of clinical importance for individuals with neurodevelopmental disorders, as cognitive performance has been shown to relate to severity of communication and social difficulties (Demetriou et al, 2018; Leung et al, 2016; Oliveras‐Rentas et al, 2012) and repetitive behaviors (Mostert‐Kerckhoffs et al, 2015), can differentiate individuals with autism spectrum disorders (ASD) (Doi et al, 2022; Nader et al, 2015; Solomon et al, 2021), potentially predict behavioral challenges, and is often used to aid diagnoses (Nader et al, 2015). As such, classifying individuals based on neurocognitive profiles could provide a framework for uncovering genetic and neurobiological differences associated with autism phenotypes, allowing for improved diagnosis and clinical outcomes.…”
Section: Introductionmentioning
confidence: 99%